The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2023
DOI: 10.1097/hep.0000000000000384
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tenofovir-based HIV pre-exposure prophylaxis against HBV infection in men who have sex with men

Abstract: Background and Aims: Men who have sex with men (MSM) are vulnerable to contracting HBV as a sexually transmitted infection. We evaluated the incidence of HBV infection (HBI) and the prophylactic effect of tenofovir-based pre-exposure prophylaxis (PrEP) on HBI in an MSM cohort. Methods and Results: MSM who were older than 16 years were enrolled from January 2018 and followed up until June 2021 and tested for HIV, bacterial sexually transmitted infections, and HBsAg/ HBsAb and HBcAb every 3 months based on inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…To the editor, We appreciate Hung and colleagues' interest in our article that examined the effect of tenofovir-based HIV pre-exposure prophylaxis (PrEP) against HBV infection in men who have sex with men (MSM). [1] We also thank them for highlighting several limitations in our study and particularly for raising a reasonable question on the prophylactic effect of PrEP against HBV.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…To the editor, We appreciate Hung and colleagues' interest in our article that examined the effect of tenofovir-based HIV pre-exposure prophylaxis (PrEP) against HBV infection in men who have sex with men (MSM). [1] We also thank them for highlighting several limitations in our study and particularly for raising a reasonable question on the prophylactic effect of PrEP against HBV.…”
mentioning
confidence: 96%
“…
To the editor, We appreciate Hung and colleagues' interest in our article that examined the effect of tenofovir-based HIV pre-exposure prophylaxis (PrEP) against HBV infection in men who have sex with men (MSM). [1] We also thank them for highlighting several limitations in our study and particularly for raising a reasonable question on the prophylactic effect of PrEP against HBV.First, they argued the possibility of a false positive result in 3 MSM defined as HBV infection based on anti-HBc antibody alone and required HBV DNA tests for them. Although HBV DNA measurements were unavailable, this serological characteristic tends to be a true positive rather than a false positive among high-risk MSM.
…”
mentioning
confidence: 96%
“…According to the article, the 22 participants who developed HBV infection were characterized. Among them, 3 (13.6%; case 5, case 6, and case 21) were positive for anti-HBc antibody alone and negative for both anti-HBs antibody and HBsAg 1 . The serologic finding of anti-HBc positivity alone could possibly be attributed to a previous HBV infection or a false-positive result, especially in those without risk factors for HBV infection in countries with low HBV prevalence 2 .…”
mentioning
confidence: 96%
“…We read with great interest the article “Effect of tenofovir-based HIV pre-exposure prophylaxis against HBV infection in men who have sex with men” by Mizushima Daisuke et al 1 We appreciate the authors’ efforts to demonstrate the prophylactic effect of tenofovir-based pre-exposure prophylaxis against HBV infection among men who have sex with men in a real-world setting. However, we believe that certain issues need to be addressed to strengthen the conclusions of the study.…”
mentioning
confidence: 99%
“…In this issue, Mizushima et al 8 demonstrated in a real-world setting that TFV-based PrEP prevented incident HBV infections among HIV-negative MSM at a high risk. In this study, the serologic markers of HBV (HBsAg; HBcAb, and HBsAb) were prospectively tested every 3 months along with tests for HIV and other bacterial STIs, which could ensure a more precise and frequent detection of asymptomatic infections.…”
mentioning
confidence: 99%